To generate greater economic benefits from visiting ships : to improve Singapore's cruise industry - Zhang, Jiawei (2017)
Singapore is a major port in the world, as well as the bridge between East and West. Port of Singapore contributes tremendously to the development of Singapore’s shipping industry, as well as the economy as a whole. However, with the downturn of maritime industry in recent years, it is vital for Singapore to re-gain the momentum of moving forward. Due to the nature of Singapore, especially the limited land and natural resources, the development of Singapore relies greatly on communications and trading with other countries. In the case of port of Singapore, its development requires the help from visiting ships. This paper will focus on how to generate greater economic benefits from visiting cruise vessels. The feasibility of this choice was proven by the rapid growth of cruising in Southeast Asia, which provides a promising outlook to the industry. In the meantime, there are many possible business opportunities that may further facilitate its growth in upcoming decades that could bring substantial benefit to Singapore. With feasibility of the idea being proved, a Porter’s Diamond Model analysis was then conducted in order to assess the competitiveness of Singapore’s cruise industry, and to indicate the restrictive factors that could limit Singapore’s cruise industry from further development. A survey to cruise passengers regarding these factors was then conducted. The results were used to analyze the level of importance and urgency to eliminate these factors. The results were as well used to categorize passengers by demographic features and purpose of traveling, in order to better understand their needs. At last, a series of recommendations were raised to eliminate the restrictive factors. All in all, the research provides an optimistic outlook for Singapore’s cruise industry. With actions and efforts taken by various parties in the industry, cruising could become a larger contributor to Singapore’s economy.